2018
DOI: 10.1136/bmjopen-2017-019672
|View full text |Cite
|
Sign up to set email alerts
|

Resuming anticoagulants after anticoagulation-associated intracranial haemorrhage: systematic review and meta-analysis

Abstract: ObjectiveTo determine the adverse outcomes following resumption of anticoagulation in patients with anticoagulation-associated intracranial haemorrhage (ICH).DesignWe performed a systematic review and meta-analysis in this clinical population. The Preferred Reporting Items for Systemic Reviews and Meta-Analyses statement was followed, and two authors independently assessed eligibility of all retrieved studies and extracted data.Data sourcesMedline, Embase and the Cochrane Central Register of Controlled Trials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…It was decided that despite the history of multiple PEs, anticoagulation therapy should be stopped acutely and an IVC filter was placed while treatment was pursued for the CCM. Current guidelines according to the American Heart Association suggest that anticoagulation could be resumed four weeks post-ICH but there seems to be a lack of consensus regarding this topic [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was decided that despite the history of multiple PEs, anticoagulation therapy should be stopped acutely and an IVC filter was placed while treatment was pursued for the CCM. Current guidelines according to the American Heart Association suggest that anticoagulation could be resumed four weeks post-ICH but there seems to be a lack of consensus regarding this topic [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…This case also highlights the need for systematic studies to better outline when to restart anticoagulation per specific risk factors (especially location) post ICH. While the American Heart Association suggests four weeks post ICH to resume anticoagulation, a meta-analysis by Zhou et al suggested there is still no firm time table when to resume therapy and further studies are needed [18].…”
Section: Discussionmentioning
confidence: 99%
“…17 Summing up these data several meta-analyses of aggregate data reported that resuming OAC was associated with significant reductions of thromboembolic events and/or ischemic stroke whereas bleeding complications and/or recurrence of intracranial hemorrhages were not significantly increased. 2528 Further, the use of antiplatelet agents did not confer benefit neither for prevention of ICH recurrence nor protection from ischemic events.…”
Section: Resuming Oral Anticoagulation After Ichmentioning
confidence: 94%
“…Several meta-analyses of reported data have been conducted until now, all of them showing a significant reduction of thromboembolic complications without leading to increased risk of ICH recurrence [ 3 , 22 , 30 , 57 ]. Furthermore, antiplatelet agents – sometimes considered as a safer alternative approach – were not beneficial neither for thromboembolism prophylaxis nor prevention of ICH recurrence [ 22 ].…”
Section: Background – Intracerebral Hemorrhage and Oral Anticoagulatimentioning
confidence: 99%